Parental substance and alcohol abuse: Two ethical frameworks to assess whether and how intervention is appropriate - Snoek, Anke (Bioethics, 2021)
Ethical frameworks can support professionals’ decision-making. Here, we identify two ethical frameworks to analyse the best support for families that struggle with parental substance or alcohol abuse. The first framework, which we call ‘the framework of conflicting interests’, is most prominent in the literature. Here, the interests of parents and children are weighed against each other using the medical ethical principles of respect for autonomy, justice, beneficence, and non-maleficence. The second framework is most prominent in a series of interviews we conducted with alcohol-dependent parents and professionals working in addiction care and youth care. This framework aligns more with an ethics of care, and starts with the assumption that the interests of people who are close to each other are often intertwined. This framework does not so much look at conflicting interests, but at relationships and vulnerability. We label this the ethics of care framework. In this article, we show the value of both frameworks and how they can support ethical decision-making.